A Novel Hybrid‐Structured Titanium Surface Promotes Adhesion of Human Dermal Fibroblasts and Osteogenesis of Human Mesenchymal Stem Cells while Reducing S. epidermidis Biofilm Accumulation2. Issue 4 (1st October 2015) - Park, Byung‐Wook; Krieger, Jessica; Sondag, Gregory R.; Moussa, Fouad M.; Rankenberg, Johanna; Safadi, Fayez F.; Gatsonis, Nikolaos A.; McGimpsey, W. Grant; Lambert, Christopher R.; Malcuit, Christopher
Abstract : We provide a comparative analysis of protein adsorption, primary human cell behavior, and biofilm formation on modified titanium substrates of either micro‐, nano‐, or hybrid micro/nano‐scale feature sizes. While studies revealed that nano‐scale structures initially decreased the attachment and spreading of both human fibroblasts (hDFs) and mesenchymal stem cells (hMSCs), hMSC differentiation studies revealed that hybrid structures promoted the highest levels of osteogenic gene expression and attenuated biofilm formation by Staphylococcus epidermidis . Taken together, this novel approach of generating a hybrid topographical feature results in a potential implant material capable of enhanced dermal cell adhesion and osteogenic differentiation while limiting biofilm accumulation. Abstract : This article examines the synergist effect of a combined micro‐ and nano‐structured titanium surface on the attachment of human dermal fibroblasts, the osteogenic potential of human mesenchymal stem cells, and the capacity to resist biofilm accumulation by Staphylococcus epidermidis .